Búsqueda de neutrinos pesados vía vértices desplazados en procesos de fusión de bosones vectoriales en colisionadores - Masias Teves, Joaquin Aurelio (Pontificia Universidad Católica del Perú, 2019)
The Standard Model (SM) is the theory that describes elementary particles and their fundamental interactions. In the Standard Model neutrinos are massless particles. Nevertheless, this has been proven wrong by neutrino oscillation experiments. Neutrinos possess mass, but several orders of magnitude below those of the other SM fermions. This invites the consideration of new physics, beyond that described by the SM, that could explain the smallness of neutrino mass. This is achieved, in particular, in the Type-1 Seesaw model, which is the focus of this work. Neutrinos are especially difficult to detect in colliders, since they are chargeless, they leave no tracks, and no energy in the calorimeters. However, if massive enough, these new neutrinos can decay into charged particles inside the collider, which results in tracks with displaced vertices. A complete analysis of this processes is required in order to characterize the parameters of these new particles. In this work we use the MonteCarlo simulation program MadGraph to study the relevant processes that involve these neutrinos. The principal objective of this work is to define the probability to observe the heavy neutrinos as Higgs decay products in the LHC (and HL-LHC), when they have been produced via vector boson fusion (VBF) and are in the section of parameter space useful for displaced vertices.
Keywords: Neutrinos; Física de neutrinos; Física de partículas; https://purl.org/pe-repo/ocde/ford#1.03.00